2010
DOI: 10.2353/ajpath.2010.090945
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Comorbidity between Opioid Drug Abuse and HIV-1 Tat

Abstract: HIV-1 infection predisposes the central nervous system to damage by opportunistic infections and environmental insults. Such maladaptive plasticity may underlie the exaggerated comorbidity seen with HIV-1 infection and opioid abuse. Although morphine and HIV-1 Tat synergize at high concentrations to increase neuronal death in vitro, we questioned whether chronic low Tat exposure in vivo might contribute to the spectrum of neuropathology through sublethal neuronal injury. We used a doxycycline-driven, inducible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
107
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 132 publications
(122 citation statements)
references
References 95 publications
13
107
2
Order By: Relevance
“…However, the 19 kDa band co-varies with expected Tat expression. The discrepancy in molecular weight may be attributed to post-translational modification of Tat and is consistent with other weights so reported (Carey et al 2012; Fitting et al 2010; Park et al 2000). Despite the need for better antibodies to Tat, the expression of this protein in the GT-tg mouse (Kim et al 2003) is generally consistent with unbound concentrations observed in HIV-positive sera (Westendorp et al 1995; Xiao et al 2000).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…However, the 19 kDa band co-varies with expected Tat expression. The discrepancy in molecular weight may be attributed to post-translational modification of Tat and is consistent with other weights so reported (Carey et al 2012; Fitting et al 2010; Park et al 2000). Despite the need for better antibodies to Tat, the expression of this protein in the GT-tg mouse (Kim et al 2003) is generally consistent with unbound concentrations observed in HIV-positive sera (Westendorp et al 1995; Xiao et al 2000).…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, expression of Tat 1-86 protein was transient, as antibody labeling declined one week after induction and did not differ from control levels two weeks after induction. Despite the known difficulties in conducting protein analyses of in vivo Tat expression, we and others have previously demonstrated similar effects (Carey et al 2012; Fitting et al 2010; Kim et al 2003). Many of the available Tat antibodies generate nonspecific labeling at the predicted weights of Tat protein (14 kDa; Fitting et al 2010 and Carey et al 2012, supplemental material), and indeed nonspecific labeling at 14 kDa was again detected herein, even among control C57BL/6J brain samples that lack Tat protein.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Moreover, Tat protein-induced synaptodendritic damage occurs prior to cell death, at very low Tat concentrations, and may be reversible [220]. Synaptic alterations in pyramidal cells of the hippocampus [221], as well as decreased spine density in medium spiny neurons [222], have also been reported in mice conditionally expressing the HIV-1 Tat protein in astrocytes. Similarly, we have recently reported that HIV-1 Tg rats have altered dendritic spines in the nucleus accumbens medium spiny neurons [159].…”
Section: Treatment Possibilitiesmentioning
confidence: 99%